Assessment basics: How to implement an effective student learning assessment process - Frederick Burrack (Academic Chairpersons Conference Proceedings, 2022)
Assessment Basics is a workshop focused on understanding the purpose behind student learning assessment, strategies to guide curricular integration, and techniques to use data for program improvement. Participants will be involved in leadership techniques to transfer into their own context. Experience with assessment processes will enable academic chairpersons with skills to guide faculty involvement and promote self-review of data that leads to continual program improvement. Assessments in higher education are crucial in providing indicators of the educational effectiveness and quality of its educational offerings. Assessments help students, instructors, and administrators answer various questions about student development, the value of specific courses, and the credibility of an institution. This session will enable participants to understand the foundation of learning expected in their program. Strategies to involve faculty in defining programmatic learning expectations reflecting course outcomes lead to the construction a curricular structure designed to guide student learning. Processes shared can guide assessment of individual student learning within courses to provide achievement data that can document program effectiveness and guide improvement decisions. Participants experience assessment tools that provide valid data to measure how well a program prepares students for educational and career-relevant learning objectives, as well as confirm applied transfer of general education learning expectations. Examples of automated data collection and reporting provides insights toward an integrated culture of assessment and continual improvement. Techniques experienced provides students with evidence of their development across courses, provides faculty with actionable feedback over time, and provides academic leaders with insight into how well students are performing against program learning objectives that can inform remediation efforts needed to address development gaps and improve educational quality. The session will be recorded, edited, and posted with the associated document to enable participants’ enhanced learning, as well as the opportunity to transfer the suggestions into each academic chairperson’s context.
Keywords: Assessment; Leadership; Learning; Effectiveness